Hubungan Perceived Service Quality Dan Loyalitas: Peran Trust Dan Satisfaction Sebagai Mediator - Licen Indahwati Darsono (BIP's JURNAL BISNIS PERSPEKTIF, 2010)
Customer loyalty is the most valuable asset for the company. Several previous studies find that customer loyalty has a positive effect on company's profitability. But, in today marketplace, managing customer loyalty is a daunting task. Marketer must clearly understand the loyalty concept, so they can find out loyalty's antecedent and manage loyalty from that antecedent. The purpose of this research is to investigate perceived service quality, trust, and satisfaction contribution to the loyalty creation. The object of this research is higher education institution, and the subjects are undergraduate students at Widya Mandala Catholic University. Reliability and validity check find that research instrument has achieved reliability, convergent validity, and discriminant validity criteria. The results support all hypotheses with the exception for perceived service quality-loyalty relationship. Perceived service quality does not have significant direct effect on loyalty. Therefore, perceived service quality does not have direct contribution for loyalty building, the contribution is indirect through satisfaction and trust. The results also find a strong support about satisfaction and trust role as a mediator of perceived service quality-loyalty relationships.